Abordagens musicais onipresentes da segunda onda para o compartilhamento de conhecimento - Keller , Damián; Costalonga , Leandro (Farol, 2024)
This paper describes two ubiquitous music (ubimus) environments that foster knowledge creation and resource sharing. The proposed designs tackle knowledge production support taking into account the embedded-embodied nature of musical activity and the community-based aspects of meaningful mutual engagements. The first case deals with deployments of the jam2jam system in formal and informal educational settings, emphasizing the role of listening as a strategy for knowledge generation. The second example targets the design of a creativite-action metaphor that makes use of environmental sonic cues for aesthetic decision-making – time tagging. We place the problem of knowledge sharing within the context of current theoretical approaches to creativity. The results indicate that creative musical activities may involve the usage of environmental cues and intense social interactions. These aspects need to be addressed when designing support technologies for creative action.